Społeczno-ekonomiczny rozwój ASEAN w świetle badań taksonomicznych - Pawlas, Iwona (ASEAN socio-economic development in the light of taxonomic research, 2009)
Processes of regional economic integration can be observed all over the world. When integration block embraces both developed and developing countries with strong political, cultural and economic differentiation the shortage of socio-economic cohesion becomes a problem. ASEAN’s enlargement has resulted in a considerable rise of inner diversity of the block. The paper presents the results of research on the level and degree of socio-economic cohesion of ASEAN. The analysis has been based on more than ten indices of social and economic development. An attempt has also been made to apply one of taxonomic methods, i.e. Z. Hellwig’s taxonomic measure of development for the evaluation of socio-economic development of ASEAN member economies. In addition to that the achieved results have been compared with the positions of ASEAN countries in the Global Competitiveness Report, Human Development Report, the Global Information Technology Report as well as Travel and Tourism Competitiveness Report
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 67, s. 51-61